Speech Acts of Apology and Regret Expressions Used by English Language Students at Al al-Bayt University (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This study aimed to identify the use of apology and regret speech acts among bachelor students majoring in English language and literature at Al al-Bayt University, It examines the functions of apology and regret speech acts based on Searle's (1979), and Cohen & Olshtain (1983) taxonomy regarding the apology strategies, It also the study aims to contribute valuable insights and information regarding the use of apology and regret speech acts, considering the variables gender and place of residence. It employs mixed methods, collecting data from 60 students through 20 Discourse Completion Tasks (DCTs) focused on academic issues. The findings reveal variations in the use of speech act functions and strategies between male and female students, as well as differences based on the place of residence, and the results suggest that gender socialization and cultural expectations influence the speech act preferences of students. Both genders prioritize different functions and strategies, reflecting societal norms and communication styles . Additionally, variations in the use of speech acts are observed between village and city residents, influenced by the rural and urban environments.